Ventricular septal rupture after blunt chest trauma: a case report - Masato Tochii; Hirotaka Watanuki; Kayo Sugiyama; Yasuhiro Futamura; Hiroshi Ishikawa; Katsuhiko Matsuyama (Surgical Case Reports)
Abstract Cardiac injury, including myocardial contusion and valvular damage, is a common complication of blunt chest trauma; however, traumatic ventricular septal rupture is a rare complication. We encountered a rare case of ventricular septal rupture following blunt chest trauma that was successfully repaired by emergency surgery. The mechanism underlying rupture may involve acute compression of the heart between the sternum and the vertebral column when the ventricle is filled, thereby causing a sudden increase in intraventricular pressure and leading to septal rupture. Emergency operation should be considered in cases of large defects and hemodynamic instability.